2012
DOI: 10.1002/ijch.201200005
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Analog Calcipotriol Combined with Aminolevulinate‐Mediated Photodynamic Therapy for Human Psoriasis: A Proof‐of‐Principle Study

Abstract: We previously showed that select agents (methotrexate or Vitamin D), when administered as a preconditioning regimen, are capable of promoting cellular differentiation of epithelial cancer cells while simultaneously enhancing the efficacy of 5-aminolevulinic acid (ALA)-mediated photodynamic therapy (PDT). In solid tumors, pretreatment with Vitamin D simultaneously promotes cellular differentiation and leads to selective accumulation of target porphyrins (mainly protoporphyrin IX, PpIX) within diseased tissue. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…More novel was our demonstration that 5FU stimulates tumor-selective increases in PpIX accumulation. Target tissue selectivity is a feature previously reported for other neoadjuvants such as methotrexate (18) and calcitriol in human psoriasis (29) and murine squamous cell carcinomas (24). Enhanced accumulation in tumor cells is important, but even more important may be the fact that 5-FU improves PpIX homogeneously within all cells in the tumor.…”
Section: Discussionmentioning
confidence: 62%
“…More novel was our demonstration that 5FU stimulates tumor-selective increases in PpIX accumulation. Target tissue selectivity is a feature previously reported for other neoadjuvants such as methotrexate (18) and calcitriol in human psoriasis (29) and murine squamous cell carcinomas (24). Enhanced accumulation in tumor cells is important, but even more important may be the fact that 5-FU improves PpIX homogeneously within all cells in the tumor.…”
Section: Discussionmentioning
confidence: 62%
“…ALA‐PDT offers the advantage of dual selectivity, because both the PpIX and the visible light can be localized to the tumor, minimizing any damage to the normal tissue. In dermatology clinics, ALA‐PDT is successfully used for treatment of actinic keratosis (sun‐induced precancers) and squamous carcinoma in situ .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells often bypass normal physiological controls on pathways of growth, differentiation and survival to circumvent the cell death and the concept of cPDT is to counteract these abnormalities, using selected small molecule agents. Thus, we found that certain differentiation promoting agents such as methotrexate (MTX) , vitamin D 3 and 5‐fluorouracil (5‐FU) , when given prior to ALA‐PDT, make cancer cells more susceptible to cell killing through accumulation of higher levels of PpIX. We have successfully tested the cPDT concept in various preclinical models including cultured cells , 3D organotypic models in vitro and murine tumor models in vivo , using MTX, vitamin D 3 , or 5‐FU in a 3‐day pretreatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Cells that are poorly differentiated and rapidly proliferating, as is common in many tumors, may produce insufficient amounts of PpIX . One area of investigation to address this issue involves the use of cellular differentiators such as vitamin D or its analogues, methotrexate, retinoic acid, 5‐fluorouracil acid, iron chelators and the androgens 5α‐dihydrotestosterone (DHT) and R1881 .…”
Section: Targeting the Tumor Microenvironment With Photochemistrymentioning
confidence: 99%